2020
DOI: 10.1101/2020.02.03.931949
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deficiency of complement component C1Q prevents cerebrovascular damage and white matter loss in a mouse model of chronic obesity

Abstract: ABSTRACTAge-related cognitive decline and many dementias involve complex interactions of both genetic and environmental risk factors. Recent evidence has demonstrated a strong association of obesity with the development of dementia. Furthermore, white matter damage is found in obese subjects and mouse models of obesity. Here, we found that components of the complement cascade, including C1QA and C3 are increased in the brain of western diet (WD)-fed obese mice, particularly in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…C1QB and C1QC belong to a family of complement proteins that are positively correlated with immune cell chemotaxis and can regulate the expression of the immune cells. Recent findings have revealed that C1Q-related gene knockouts can prevent obesity-related complications of Alzheimer’s disease ( Graham et al, 2020 ). FCGR2B and FCER1G are immunoglobulin fragments that regulate the immune response, and increase the likelihood of obese patients developing allergic diseases ( Mathur et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…C1QB and C1QC belong to a family of complement proteins that are positively correlated with immune cell chemotaxis and can regulate the expression of the immune cells. Recent findings have revealed that C1Q-related gene knockouts can prevent obesity-related complications of Alzheimer’s disease ( Graham et al, 2020 ). FCGR2B and FCER1G are immunoglobulin fragments that regulate the immune response, and increase the likelihood of obese patients developing allergic diseases ( Mathur et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Whether microglia could strip myelin off axons from live neurons remains unclear, but microglia do appear to survey myelin sheath in vivo (Zhang et al., 2019), and anti‐myelin antibodies or complement might promote such myelin stripping (DeJong & Smith, 1997; Vargas et al., 2010). Complement is activated in MS (Watkins et al., 2016), and C1q knock‐out mice were protected against white matter loss in a mouse obesity model, suggesting that C1q may mediate microglial phagocytosis of live myelin (Graham et al., 2020). Recently, it has been shown that C3, but not C1q, localize with synapses in several models of MS (Werneburg et al., 2020).…”
Section: Phagocytosis Of Neurons and Synapses In Neurodegenerationmentioning
confidence: 99%